2017
DOI: 10.1080/20550324.2017.1315210
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and organomodified nano-montmorillonite dispersions for use as supplementary cementitious materials – a novel theory based on nanostructural studies

Abstract: The compatibility of three nano-montmorillonite (NMt) dispersions in hydrating cement binders was investigated and a new theory linking the nanostructure of nanoclay dispersions to their effect on the macroscale performance of cement pastes is presented. Two aqueous organomodified NMt dispersions (one dispersed with non-ionic fatty alcohol and the other with anionic alkyl aryl sulfonate) and one aqueous inorganic NMt dispersion (dispersed with sodium tripolyphosphate) were characterized via transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…Although a number of papers have been reported on the flexural performance of binary nanosilica [34], nanotube [35], or nanoclay [36] enhanced cements, no research has been presented in ternary blends reinforced with fibers. It is acknowledged that nMt nanoparticles can improve flexural strength and assign damping properties [37] to pastes they will be added to [19]. Moreover, as stated above, nMt particles may further exfoliate within the hydrating cement matrix, dispersing in one direction under stirring [20], rendering them possibly more suitable for flexural than compressive strength enhancement.…”
Section: Manufacturing and Fabrication Methods Cement MIX Characterizamentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of papers have been reported on the flexural performance of binary nanosilica [34], nanotube [35], or nanoclay [36] enhanced cements, no research has been presented in ternary blends reinforced with fibers. It is acknowledged that nMt nanoparticles can improve flexural strength and assign damping properties [37] to pastes they will be added to [19]. Moreover, as stated above, nMt particles may further exfoliate within the hydrating cement matrix, dispersing in one direction under stirring [20], rendering them possibly more suitable for flexural than compressive strength enhancement.…”
Section: Manufacturing and Fabrication Methods Cement MIX Characterizamentioning
confidence: 99%
“…Of all nanoparticles employed in these studies, the nMt's, which are promising materials for a number of reasons, including the fact that they are naturally occurring, abundant, and cost effective, provided ambiguous results. It was found that their addition at significant concentrations can, indeed, cause a reduction in compressive strength of samples and this was attributed to a number of issues; primarily the modifier and dispersion agent used and the nanostructure of each dispersion itself [19,33], the quantity of nMt addition, and the absence of superplasticizer [1,28]. In summary, results suggest that in ternary (Portland limestone nanocomposites) [32] and quaternary combinations [1] 1% of nMt addition by total weight of the binder is optimal and can offer strength improvements in pastes.…”
Section: Manufacturing and Fabrication Methods Cement MIX Characterizamentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that even the lowest nMt addition caused a significant reduction in density could only be attributed to the poor compaction during production, resulting in a less dense paste, and possibly in an increase in the porosity. Adding to this, the characterization of the nC1 dispersion showed re-agglomerating particles, causing areas of potential weakness in pastes [5]. Hence, in this way, the low compressive strengths delivered by the nC1 addition [6] can be justified.…”
Section: -3mentioning
confidence: 94%
“…In this research three different aqueous nanomontmorillonite dispersions were used; (i) the first was dispersed with non-ionic fatty alcohol and was called nC1, (ii) the second (nC2) was dispersed with anionic alkyl aryl sulphonate and (iii) the third one (nC3), the inorganic nMt dispersion was dispersed with sodium tripolyphosphate. The process of the nMt platelet separation by using different modifiers and different dispersants and the difference between the organomodified and inorganic dispersions has been described elsewhere [1], [5]. Characterization of the three dispersions via TEM imaging and crystallography, XRD, SEM/EDX and TGA/DTG also taking into consideration results published in cement pastes lead to the following conclusions [6]:…”
Section: Introductionmentioning
confidence: 99%